Study of Ziegler-Natta/(2-PhInd)2ZrCl2 hybrid catalysts performance in slurry propylene polymerization - Gholam-Reza Nejabat (Polyolefins Journal, 2015)
Several types of hybrid catalysts are made through mixing of 4th generation Ziegler-Natta (ZN) and (2-PhInd)2ZrCl2  metallocene catalysts using triethylaluminum (TEA) as coupling agent. Response surface methodology (RSM) is used to evaluate the interactive effects of different parameters including amounts of metallocene and TEA and temperature on metallocene loading. Analyzing the amounts of Al and Zr elements in the hybrid catalysts through ICP-OES and EDXA reveals that temperature plays a crucial role on anchoring of the metallocene catalyst on ZN while TEA has the least determining effect. The ICP analysis shows that as the concentration of Al goes up in the hybrid catalyst the concentration of Zr passes a maximum, while EDXA shows a direct relationship between the Al and Zr contents. Using triisobutylaluminum (TIBA) and methylaluminoxane (MAO) as the coupling agents, almost similar metallocene loadings are observed. Finally, the performance of hybrid catalysts is investigated in propylene polymerization and the obtained polymers are characterized using DSC and DMTA through which the presence of two types of polymers in the final product are confirmed.